Numerical Analysis Of The Combustion Characteristic Of Compression-Ignition Engine For The Application Of Biodiesel - Fauzi, Farah Aina (Universiti Sains Malaysia, 2021)
Simulations and research of the internal combustion engine are being done to discover the potential ways to improve the efficiency of diesel engine. The effects that had been focused on this study is engine speeds and the injection timings on the physical behaviour in cylinder process in a diesel engine. This study stresses on the apparent heat release rate on of NOx in the cylinder. This research study implies a significant commitment in terms of time and high technology device. As a result, the simulation programmed ANSYS Fluent can be used to conduct a research on a bio-diesel engine's performance and emissions. The simulation will be conducted by setting the engine speeds of 2500rpm and injection timings CA15 BTDC using eddy dissipation model. In this study, parameters including CA, spray angle valve timing, injection velocity, and injected mass are fixed. Simulations results showed that higher engine speed in revolution per minute lowers the rate of unburnt fuel. Excess oxygen contributes in the oxidation of gaseous hydrocarbons and carbon monoxide in the exhaust gas, reducing them to extremely small amounts and resulting in lower rate of unburn fuel.